Dry Goods - Shein, James B., 1942-; Joyce, Tim; Cornuke, Brandon ([London] : SAGE, 2016)
MBA students Tim Joyce and Brandon Cornuke had what they believed was a great product concept: a body powder that could be delivered in an aerosol spray. Current market-leading powders such as Gold Bond and Johnson's Baby Powder involved messy application, as they were only available in 'dump-on' form. Worse, because powders deposited on top of the skin didn't adhere to it, they tended not to last long. Joyce and Cornuke believed an aerosol powder spray would solve these problems. They called their product concept Dry Goods. However, taking Dry Goods from idea to reality presented some serious challenges. How would two students without access to a lab be able to research and develop a complex chemical/physical process like aerosol delivery, let alone manufacture it? This case study discusses this question.
Originally Published in: Shein, J., Joyce, T., & Cornuke, B. (2010). Dry Goods. 5-210-263. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Dry Goods (Firm); New products -- Case studies; Product design -- Case studies; New business enterprises -- Case studies